RESEARCH OF DEPENDENCES OF RELIABILITY INDICATORS OF APAR ON THE CORE TEMPERATURE OF A GAN CRYSTAL TRANSISTORS - Костановський, Валерій Вікторович (Science-based technologies, 2019)
The article examines the effect of the core temperature of a crystal of the microwave transistors of the receiving-transmitting modules of active phased antenna arrays (APAR) on the reliability indices. Reliability is one of the main characteristics of the effectiveness of radar with APAR, so the proposed research topic is important and relevant. The paper analyzes mathematical models of failures and the effect of the temperature of the crystal working area on the failure rates of microwave transistors and micro-modules. An Arrhenius model is considered to determine the coefficient of temperature dependence of the working zone of a crystal of microwave transistors made by GaN technology. Models of sudden and gradual failures of microwave transistors and micro-modules are presented. Formulas are shown for the predictive estimate of the failure rates of microwave transistors and micro-modules: - in case of sudden failures (exponential distribution); - with gradual failures (non-monotonic diffusion distribution); - in case of joint manifestation of sudden and gradual failures (composition of exponential and diffusion non-monotonic distributions). On the basis of the work performed earlier by the author, the models are considered and formulas are presented for calculating the probability of failure-free operation and the mean time to failure of the receiving-transmitting module, the antenna sub-lattice, and APAR as a whole. Using the above mathematical models, we studied the change in the reliability indicators of a two-level APAR of a promising radar at various temperatures of the working zone of the crystal of the microwave transistors of the transmitting channels of the receiving and transmitting modules. Graphs of the change of the mean time to failure and the probability of failure-free operation are plotted, depending on the temperature of the working zone of the microwave transistor crystal with different types of failures: sudden, gradual, and a mixture of sudden and gradual failures. The behavior of the mean time to failure and the probability of failure-free operation of APAR from the temperature of the working zone of the microwave transistor is investigated. It is shown that with a logarithmic scale for mean time to failure all models and, accordingly, graphs are linear functions. The results obtained in the article can be useful to developers of promising radars with APAR in the design of liquid cooling systems, the correct choice of the parameters of microwave transistors in the receiving and transmitting modules and the structure of the APAR antenna array.